Experiencing the transition from childhood to adolescence: the role of consumption from the viewpoints of children and mothers - Dallolio, Adriana Schneider (2022)
This dissertation investigates the role of symbolic consumption during the liminal transition from childhood to adolescence from three distinct perspectives: the academic parent-asresearcher, mothers, and pre-adolescents themselves. Adopting the standpoint of the latest wave of New Childhood Studies, I took on the parent-research form of inquiry and engaged in ethnography to comprehend the liminal transition from childhood to adolescence. Specifically, I wanted to answer the following questions: How does consumption aid or hamper this process for children themselves and other emotionally connected participants in pre-adolescence transition, like mothers? How does consumption impact pre-adolescents and their peer socialization? How best to investigate consumption during transitions and apply child-centric methods when the researcher is a ‘native’ in the field? I explore these interrogations in three papers, each covering the viewpoint of one of the social actors involved in this study. The first paper addresses how pre-adolescent daughters’ liminal transition spillovers mothers. They transform from fully needed mothers to mothers of independent teenagers with the help of individual rituals and routines of consumption. The second paper analyzes how luxury consumption, empowered by social media, creates distinction and impacts peer group socialization in a flat environment—where individuals have balanced access to economic capital. The third paper, an autoethnography, discusses an alternative methodological approach toward studying children, introducing the experience of parent-as-researcher (PAR) and children as co-researchers. Overall, departing from a single contextual phenomenon and covering diverse enabling theories, from rituals and routines to distinction, I contribute to marketing literature by (1) Expanding the knowledge of liminal consumption, showing that liminality is a threaded phenomenon experienced simultaneously by emotionally intertwined individuals. (2) Revealing how luxury consumption, beyond ownership, subverts normative beauty standards, allowing new positive outsiders to emerge and, at the same time, intensifies the exclusion of those unable to master luxury enactment. (3) Providing an innovative methodology for childhood consumption studies, since the insiders’ approach of the PAR’s inquiry and the perspective of children as co-researchers enlighten new forms to engage children in marketing research.